Cloud Migration Strategies for EDI Transactions in Healthcare Payor Ecosystems - Gokul Ramadoss (North American Journal of Engineering Research, 2023)
For the most authentic, powerful, and reliable system that is being used for data exchange and the whole healthcare industry relies on the Electronic Data Exchange Interchange (EDI). Considering the data security, scalability, and low cost of data security, cloud migration is a brilliant idea for the healthcare industry. The migration of EDI transactions to the cloud and the steps involved during the migration are explained in this study, while focusing on the importance of planning, execution, and after migration efficiency. While going through the planning step, a detailed testing of current EDI infrastructure and stakeholder interest is very important to make a perfect and comprehensive migration plan. The most important part is selecting a suitable cloud service provider (CSP) with data security experience in the healthcare industry. The next step, which is the execution phase, involves the pre-migration assessment, which consists of data migration, smooth system integration, and checking of all security procedures. The key point is to have training staff and having a detailed documentation this will help in the perfect adoption of the system. To get familiar and get the maximum advantage out of it with the Cloud-based EDI System, this step is essential. The principle to improve the system results include regular performance assessment, security checks, monitoring costs, and collecting feedback. The phase in which the future transactions increment will be handled if at any point the organization blooms, is the Scalabilty planning. The upcoming innovations like the Artificial Intelligence (AI), Machine Learning (ML), and Internet of Things (IoT) devices, and any improved process to exchange the data will give a better view of the cloud-based EDI systems.